TANGGAP COVID - 19 MASYARAKAT DI DESA BATU KEDE KECAMATAN MASALLE KABUPATEN ENREKANG TAHUN 2020 - Esse Puji Pawenrusi; Ayu Lestari (Jurnal Pengabdian Masyarakat Gerakan Aksi Sehat (GESIT), 2021)
Corona virus disease or COVID-19 is a large family of viruses that can cause disease in animals or humans. In humans, covid is known to cause respiratory infections ranging from the common cold to more severe diseases such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory However, public awareness in DFesa Batu Kede, Masalle District, Enrekang Regency is still very low to implement health protocols to avoid the spread of the corona virus. Therefore, an understanding of the health protocol for handling COVID-19 is needed. Then the authors carry out community service through Real Work Lectures (KKN) STIK Makassar COVID-19 response which is implemented using methods to support public safety against COVID-19. Like making banners about health protocols, teaching elementary school children in CPTS practice, building hand washing posts, distributing masks to break the chain of transmission of COVID-19, and Making Toga, hopefully with this program the community can comply with health protocols.Syndrome (SARS). As a result of this activity, I managed to distribute 50 masks to vulnerable people, put up health protocol banners around residents' houses, built hand washing posts around Batu Kede Village, educated CPTS, and invited the community to make toga by applying health. protocol.